Return to Teamsterville: A reconsideration and dialogue on ethnography and critique. Issue 1 (1st January 2022) - Ward, Mark; Spencer, Leland G.; Stewart, Craig O.; Varela, Elisa M.
ABSTRACT: As the places of monuments are reconsidered today in light of social justice concerns, the authors revisit a "monument" of language and social interaction (LSI) research. Philipsen's foundational work published nearly 50 years ago, "Speaking 'Like a Man' in Teamsterville, " thus becomes a starting point for dialogue among four scholars with diverse views on the critical voice in ethnography of communication research. When read today, the homophobic speech of Teamstervillers is shocking. Also surprising by present standards is that such speech passes unremarked and does not figure in the analysis. In the present essay, the authors—an LSI scholar, discourse studies scholar, critical rhetorical scholar, and an LSI doctoral student—review early debates on the critical voice, relate individual narratives of their experiences in either reading "Teamsterville" again after a long hiatus or encountering the work for the first time, and then conduct a joint dialogue on the question: What is the ethnographer's obligation when harmful and oppressive speech is observed? Though their views remain diverse, the authors advocate for a disciplinary consensus: that the present moment calls for renewed discussion—and, even if differently practiced, affirmation—of the critical voice in the ethnography of communication.